An approach to describing the design of children’s reading and information books - Walker, Sue (InfoDesign, 2006)
This paper describes an approach to description of book design. It is part of a project that aims to develop an approach to description for identifying typical visual characteristics of children’s reading and information books from 1830 to 1960 in order to identify different or innovative approaches to design, and to identify changes over time. It proposes description of design elements at macro and micro levels under ‘document structure and articulation of content’, ‘typography’, and ‘material attributes’. In resulting descriptions it is proposed that these elements should be discussed in relation to the context of use that affects the design decisions that are made.